Kritik Hikayat Tentang Dajjal dalam Film Messiah Perspektif Hadis: Studi Literatur - Nurasiah Jamil (Jurnal Riset Agama, 2022)
Hadith is a guide other than the Qur'an that can guide Muslims to the right path. The Day of Judgment is the day of retribution for all people for the sins they have committed, and there is not a single creature on Earth who can avoid the Day of Judgment or the Day of Judgment. Recently, a phenomenal film called “Messiah” appeared on a platform that has a lot of fans, namely Netflix. This study aims to discuss the criticism of the saga about Dajjal in the film Messiah from the perspective of hadith. This study uses a qualitative approach by applying Literature review method. The results and discussion of this research are that the main player named Payam Golshiri (who plays the role of Al-Masih) in the film's storyline does not describe as al-Masih ad-Dajjal described in the hadith, based on authentic hadith such as the hadith narrated by Muslim and Bukhari. Although there are several scenes that depict Payam Golshiri, which is the character of al-Masih ad-Dajjal, they still do not fully describe the teachings of Muslims. This study finds that sagaciously, the Messiah film contains several scenes that depict Payam Golshiri as a representative of al-Masih, but cinematically, there are several events that do not depict al-Masih in hadith but rather describe ad-Dajjal such as the place where Payam Golshiri descended, resurrected the slain youth, moved as fast as the wind described by a hurricane, and the Jews followed Payam Golshiri.